Лiпiдний та лiпопротеїновий склад сироватки кровi при медикаментозному гепатитi щурiв за рiзних способiв корекцiї - Мельничук, Д.О.; Грищенко, В.А.; Литвиненко, О.М. (Видавничий дім "Академперіодика" НАН України, 2008)
The modelling of a medicamentous hepatitis at rats is accompanied by the development of dyslipidemia which can be a consequence of the infringement of digestion and the mastering of exogenous lipids of forage and their insufficient endogenous synthesis at a toxic damage of the digestive system and liver. As a correcting therapy, phospholipid-containing preparations with the reparation action, particularly the biologically active addition FLP-MD and preparation “Essentiale”, are proposed. The best efficiency is shown by FLP-MD which is produced on the basis of dairy phospholipids.